Bowman’s Paradox: Prospect-Theory-Based Risk-Return Relationship (Some Recent Evidence in Indonesia) - Nuir, Rikko Sajjad; Asri, Marwan (UI Scholars Hub, 2019)
There is extensive evidence indicating a negative risk–return relation when a ﬁrm’s performance is measured based on accounting measures, such as its Return on Assets (ROA) and Return on Equity (ROE). Previous studies show that the risk-return paradox can be explained by the prospect theory, which predicts that managers’ risk attitudes are different for ﬁrms with differing performance. This study will test whether there is a risk-return paradox in the context of Indonesian companies. This study uses ROA and its standard deviation to deﬁne return and risk. Industry level and market level median ROA are used as reference points. Three control variables (ﬁrm size, leverage as a proxy of ﬁrm risk, and company age) are included in the model to increase the robustness of this research. A new sample of nine industries (about 488 ﬁrms) over a 10-year period (2008-2017) provides strong evidence that the risk-return paradox exists in Indonesia. In particular, ﬁrms which are below their target level are found to be risk takers (Hl) while organizations above their target level are risk averse (H2); moreover, the below-target slope was generally steeper than the above-target slope (H3). These results support the basic propositions of the prospect theory.